Marketingo etika Lietuvos žiniasklaidoje: žiniasklaidos turinio vadovų ir marketingo / pardavimo vadovų etinių nuostatų palyginimas - Abromaitytė-Sereikienė, Laima (Information & Media, 2010)
Žiniasklaidos įmonės, kaip ir kitos įmonės, veikia konkurencinėje aplinkoje, siekia įgyvendinti savo tikslus, bet dėl specifinio produkto turi atlikti tam tikrą misiją. Tačiau yra situacijų, kai priimami neetiški sprendimai. Sunkmetis išryškino etinių sprendimų žiniasklaidoje stoką. Siekiant išsiaiškinti, kaip gerinti situaciją, būtina įvertinti esamą padėtį ir nustatyti veiksnius, darančius įtaką Lietuvos žiniasklaidos įmonių marketingo sprendimų etiškumui. Atsižvelgiant į tai, kad žiniasklaida veikia dvigubo produkto rinkoje, šiame darbe pristatoma ir analizuojama abu produktus gaminant / parduodant dalyvaujančių asmenų grupių – žurnalistų, kuriančių žiniasklaidos turinį, ir marketingo / pardavimo specialistų, parduodančių pritrauktą auditorijos dėmesį, vadovų nuomonė.Pagrindiniai žodžiai: marketingas, etika, žiniasklaida, Lietuva.Ethical Rules of Marketing in Lithuanian Media Companies: Comparison of the Ethic Principles of Media Content Managers and Media Marketing / Sell ManagersLaima Abromaitytė-SereikienėSummaryMedia companies, like all other companies, operate in the competitive environment and seek their own purposes. Considering the fact that these companies produce a specific product, they accomplish, or should accomplish, a specific mission – to serve the interests of society. However, the products produced by the media not always match the interests of society.To assess the state of marketing ethic of the Lithuanian media means, of the actions that have the biggest influence on ethical decisions, quantitative media companies’ a research was performed in November–December 2006 by e-mail. Taking into consideration the operation of media companies in a double product market, two groups of persons were investigated: (1) persons responsible for media content, (2) persons responsible for media marketing/sales. The research embraced all media companies operating in Lithuania.The respondents have agreed that unethical behaviour in the Lithuanian media sector does exist. Managers have a stronger opinion on this matter. Most of the respondents have said they always or in general behave ethically in their working life. No statistically significant difference has been established in how journalists and marketing professionals understand ethical rules.